A study on clinical profile of meconium aspiration syndrome in relation to gestational age and birth weight and their immediate outcome - V., Manivannan; R., Jegan Murugan; S., Devandiran R. (International Journal of Contemporary Pediatrics, 2019)
Background: Aim of the study was to understand the factors causing meconium aspiration syndrome (MAS) in relation to gestational age and birth weight and their immediate outcome. Methods: This study was done on babies admitted in the neonatal intensive care unit (NICU) of Thanjavur medical college hospital, who fulfilled the criteria of MAS. Babies born with meconium stained amniotic fluid (MSAF), were resuscitated as per NRP guidelines. The babies with complications of MAS were admitted to NICU and were observed for their immediate outcome in the hospital. Results: MAS occurred most commonly in babies having fetal distress and in mothers with history of PIH. It is seen more commonly in babies born through caesarean section and in term babies with mean gestational age of 38-40 weeks of gestation and mean birth weight of 2.71 kg. Most babies were depressed at birth and most common cause of mortality was hypoxic ischemic encephalopathy (HIE stage III), significantly contributing 37.5% of cases of MAS. There was significant and strong association between the birth weight and mortality. Thick MSAF was significantly associated with need for mechanical ventilation and subsequently higher mortality. Babies born through caesarean section with MAS also had significantly poor outcome. Conclusions: MAS is an entity which is commonly seen in term and post term babies with birth weight >2.5 kg. There is a significant correlation between the birth weight and outcome in MAS. When thick meconium stained liquor is noted prior to birth, anticipation is necessary and non vigorous babies need aggressive management and possibly early ventilation. Asphyxiated babies should be followed up astutely. Continuous monitoring and early intervention, followed by due resuscitation as per guidelines can reduce the morbidity, complications and the mortality in MAS.